SNP fingerprinting and farmer criteria for selection, multiplication, and traceability of cacao in Nicaragua - Bordeaux, Mélanie (2023)
Introduction. Genetic diversity, registration, and traceability of cacao planting material are the essential tripod to support its sustainable cultivation. In Nicaragua, cocoa planting material is mostly obtained from seeds, which leads to great variability in yield, bean quality, and tolerance to pests and diseases. Farmers, technical staff, development projects, and investors depend on a limited supply of elite trees as a reliable source of genetic material to support new cacao fronts and meet market quality standards. Therefore, the development of a national genetic improvement program and a planting material traceability system in Nicaragua are necessary to improve the sustainability of cacao cultivation. Objective. To evaluate the genetic resources on farms and provide information for future breeding programs, as well as to lay foundation for a national traceability and certification system. Materials and methods. Fourty-nine elite trees selected by farmers in the main producing regions in Nicaragua between 2018 and 2020 were sampled. Ninety-three SNP markers were used to characterize them and resolve their genetic origins. Results. The evaluated cacao trees had a narrow genetic background, mainly composed of hybrids with Amelonado (36 %), Criollo (17 %) and Iquitos (15 %) origins. A set of trees with high genetic diversity that could be incorporated into a selection and breeding program was identified. Conclusion. Fingerprinting with SNP markers was a useful tool for evaluating the genetic links of cultivated cacao and can be used for varietal identity test at the farm level. The study provided the basis for developing both a breeding program and a traceability system of cacao planting material in Nicaragua.